(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
Several excavations in Slovakia resulted in the finding and description of a new species of the extinct phocid subfamily Devinophocinae from the early Badenian, early Middle Miocene (16.26-14.89 Ma). Material of Devinophoca , including the skull, mandibles and teeth, presents distinguishing characters of the subfamily as well as mixed characters with the three extant phocid subfamilies (Cystophorinae, Monachinae and Phocinae). Detailed descriptions of dentition reveal that true seals ranging from 16 million years ago to the present have a generally uniform dental formula within each subfamily, based on total number of incisors: Phocinae (10 incisors; 3/2), Cystophorinae (6 incisors; 2/1); Monachinae (8 incisors; 2/2), and Devinophocinae (also 8 incisors as Monachinae, but in different combination: 3/1). The newly described Devinophoca emryi is represented by the second known skull of this subfamily, with D . claytoni being the first. Certain derived characters in pinnipeds were clearly noticeable on this skull, supporting the phylogenetic analysis that showed D . claytoni as its sister taxon. Stratigraphical examinations suggest that these Paratethyan seals ( D . claytoni and D . emryi )from the Vienna Basin, specifically from the Dev√≠nska Nov√° Ves-Bonanza locality, occupied shallow marine water with coral-reef zones. Over time, they transitioned from a humid, tropical shallow shore zone in the early Badenian (16.26 ‚Äì 14.89 Ma) to a subtropical climate in the middle Badenian (14.89 -13.82 Ma) and a warm temperate climate during the late Badenian (13.82 -12.73Ma).